The influence of dexamethasone treatment and successive road transport stress on the occurrence of caprine pneumonia in a hot humid tropical environment - Emikpe, Benjamin Obukowho; Tanko, Polycarp Nwunuji; Onilude, Opeyemi Mayowa; Mohd Yusoff, Md Sabri (Veterinary World, 2013)
Aim: The information on the effect of multiple stress and caprine pneumonia especially in a hot humid environment is limited in literature. Materials and Methods: Sixteen goats were divided into 4 groups. Group A were subjected to 8 hours and 3 hours transportation, group B to 8 hours transport stress once and dexamethasone injection, group C to 8 hours transport only while group D was the control. All goats were observed for respiratory signs while temperature was monitored daily. Dead ones were necropsied while the survivors and the goats in group D were sacrificed on day 21. The clinical, gross, histopathological, immunohistochemical scores were according to standard methods. Results: The mean total clinical score was higher in group B than group A, C and D. Two goats of the groups A, B and C goats died 21, 14 and 7 days post treatment. The dead goats in groups A, B, C had lung lesions typical of pneumonic pasteurellosis. An average of the lung consolidation of dead animals in group A was 15%, in group B, 8.5% and group C, 6.5% mostly involving the anterior and ventral part of the lung. The immunostaining results was also similar with all the lung samples positive for both Pasteurella multocida and Mannheimia haemolytica especially in the groups A, B, C with enhanced severity in A > B > C. Conclusion: This further buttress the need to reduce stress in farm animals and the emergence of P. multocida over M. haemolytica in the epidemiology of bacterial caprine pneumonia in stressed goats in Malaysia.